Gene Expression of Extracellular Matrix Proteins, MMPs, and TIMPs in Post-Operative Tissues of Chronic Rhinosinusitis Patients - Zygimantas Vaitkus; Astra Vitkauskiene; Liutauras Labanauskas; Justinas Vaitkus; Povilas Lozovskis; Saulius Vaitkus; Ieva Janulaityte (Cells)
Chronic rhinosinusitis (CRS) is a persistent inflammatory condition of the sinus mucosa characterized by significant tissue remodeling. This study aimed to evaluate the gene expression of extracellular matrix (ECM) proteins, matrix metalloproteinases (MMPs), and tissue inhibitors of metalloproteinases (TIMPs) in post-operative tissues of CRS patients. A total of 30 patients diagnosed with CRS, divided into CRSwNP (with nasal polyps) and CRSsNP (without nasal polyps) groups, were compared with a control group of 10 individuals undergoing nasal surgeries for non-CRS conditions. Gene expression analysis was conducted using quantitative real-time PCR, and plasma cytokine levels were measured via ELISA. Results indicated significantly higher expression of collagen I, collagen III, fibronectin, vimentin, periostin, and tenascin C in CRS tissues, especially in CRSsNP patients. Conversely, elastin expression was markedly lower. MMP-2, MMP-9, TIMP-1, and TIMP-2 expression was significantly altered, with CRSsNP showing lower levels compared to CRSwNP and controls. TGF-β1 expression was elevated in both CRS groups, particularly in CRSsNP, highlighting its role in fibrosis and ECM remodeling. Additionally, increased plasma concentrations of TSLP and TGF-β1 suggest epithelial activation and immune dysregulation in CRS. These findings underscore distinct remodeling profiles in CRS endotypes, emphasizing the need for targeted therapeutic strategies based on molecular phenotyping. Understanding ECM dysregulation and inflammatory pathways in CRS may lead to improved, individualized treatment approaches.